The Determinants of Non-Performing Loans: Evidence from African Banking Systems - Paul, Michael (Department of Finance and Tax, 2023)
Historically, the evolution of NPLs across different regions has been relatively heterogenous, in part due to unique structural differences that comprise different banking sectors and the varying impact that certain macroeconomic conditions have on different countries' banking systems. This study empirically investigates the leading determinants of credit risk in the African context by employing the ARDL approach to cointegration on eight African countries: Egypt and Morocco (North African countries), Botswana and South Africa (Southern African countries), Kenya and Mauritius (East African countries), and Ghana and Nigeria (West African countries). Due to data availability and reliability concerns quarterly data is used in Egypt (Q1 2009 – Q4 2020), Morocco (Q1 2005 – Q4 2020), Botswana (Q1 2007 – Q4 2020), Kenya (Q1 2009 – Q4 2020), Mauritius (Q1 2009 – Q4 2020), Ghana (Q1 2008 – Q4 2020), and Nigeria (Q1 2010 – Q4 2020). Monthly data is used in South Africa (December 2012 – December 2020). The study aims to examine how certain macroeconomic and banking industry specific factors uniquely impact the accumulation of NPLs across different African regions. In addition, an external variable accounting for the implementation of IFRS 9 is introduced as a dummy variable. The findings indicate that macroeconomic factors are critical determinants of NPLs in the case of North African countries in both the long-run and short-run. As for the Southern African countries, NPL fluctuations are highly sensitive to banking industry-specific factors rather than macroeconomic factors. This indicates that NPLs in the Southern African banking systems are less vulnerable to adverse macro-financial shocks but rather more exposed to problems originating from the banking sector itself. In the case of the East and West African banking systems, NPLs are driven by banking industry-specific factors in the short-run but not in the long-run. Lastly, the findings indicate that the implementation of IFRS 9 has a decreasing effect on NPLs in both the short run and long run in the case of Egypt, South Africa, and Mauritius. As for Kenya, IFRS 9 seems only a critical determinant of NPLs in the long-run but not the short-run. Drawing on these results, this study recommends the promotion of a positive environment for economic growth in the case of North African countries, and the strengthening of banks' balance sheets in the case of the South, East, and West African countries.